LITHOLOGIC ORDER MAPPING AND ROCK RESOURCES INVENTORY OF KUTAWARINGIN QUADRANGLE, WEST JAVA - Ganjar Gani, Reza Mohammad; Firmansyah, Yusi; Nurdrajat, Aji (Journal of Geological Sciences and Applied Geology, 2018)
In general, the southern part of Bandung is composed of rocks produced by volcanic activity. Research in this region based on the want to understand the geology of volcanoes in Bandung and surrounding areas including the origin of the formation of the Bandung Basin (Bronto & Hartono, 2006). The Bandung basin is almost surrounded by volcanoes; even in the midst there is also volcanic rock (Silitonga, 1973, Alzwar drr., 1992). Information about why and how the area of Bandung to be controlled by volcanic rocks is needed to find out more potential resources as well as geological disasters due to volcanic activity. This study aims to decide the history of volcanism in South Bandung. I want to represent a complex area seen from the diversity of geological and rock environment conditions. This diversity condition controls the landscape and geological conditions observed at this time. The purpose of the preparation of this study is to be used to develop the Stratigraphic order and inventory of minerals.Keywords: Kutawaringin, stratigraphy, resource potential